Rewriting Gregory the Great: the Prison Analogy in Napier Homily I. (20th August 2016) - Thomas, Daniel
Abstract : The Old English homily known as Napier I survives in two distinct versions. At the heart of each version is a reworking of the opening chapter of Book IV of the Dialogi of Gregory the Great, the focus of which is an analogy comparing the epistemological limits facing humanity to the situation of a youth born in prison. Scholarly attention has focused primarily upon the different continuations of the two versions of Napier I and their connections to Archbishop Wulfstan II of York. This article, however, is primarily concerned with the reworking of the Dialogi in the early part of the homily. My analysis shows how the Anglo-Saxon homilist consistently reworks Gregory's Latin in ways that reflect the different concerns of the two writers. Where Gregory was concerned with providing reasoned, intellectual arguments to support belief in the mysteries of the faith, the author of the common core of Napier I adapts the Latin text for preaching purposes. As such, the text of Napier homily I both witnesses the importance of the Dialogi as a source in Anglo-Saxon England and provides an insight into the freedom with which such authoritative Latin sources could be adapted and reshaped by vernacular homilists.